PERTIMBANGAN HAKIM PENGADILAN NEGERI SURAKARTA DALAM MEMUTUS PERKARA PERSETUBUHAN OLEH ANAK - Afif Falady Al Rasyid; Bambang Santoso (Sebelas Maret University, 2023)
This legal research aims to analyze the considerations of judges in imposing sentencing decisions against children in conflict with the law in cases of intercourse. The purpose of writing this law is to find out how the judge considers in deciding cases of sexual intercourse committed by children. This type of research uses normative legal research methods with a prescriptive or applied case approach. The method of collecting legal materials is by means of literature study and the legal materials used are primary and secondary legal materials. The results of the study show that the considerations in the decision handed down by the judge in cases of sexual intercourse committed by children are based on Decision No. 7/Pid.Sus-Anak/2021/PN Skt complies with the legal provisions of Article 183 of the Criminal Procedure Code, Article 81 paragraph (2) of Law No. 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection, and also Article 71 paragraph (3) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, bearing in mind that minors may not receive imprisonment like adults so that they can continue their lives by becoming better individuals.Keywords: Child; sentencing; Intercourse; Judge's Consideration